SEO strategies for librarians - Vállez, Mari; Lopezosa, Carlos (Infonomy, 2024)
The main techniques and aspects to consider when starting to implement SEO strategies in libraries are presented. The process begins with an audit to assess the situation, and from there, it addresses the different elements to apply. It concludes by highlighting the importance of quality content, which should undergo continuous evaluation and review.